Saponins; a ubiquitous phytochemical: A review of its biochemical, physiological and pharmacological effects. (2014)
Saponins are ubiquitous phytochemicals widely reported to be present in many species of plants and animals. Some saponin containing plants, mainly legumes, have been used as animal feed, but others are toxic. In this review, the biochemical, physiological and pharmacological effects of saponins in humans and animals have been highlighted. Physiological and biochemical effects examined include the effects on biological membranes, gastrointestinal absorption, blood and liver cholesterol, enzymes and general body metabolism, reproductive, antioxidant and free-radical scavenging effect, smooth muscle activity and effects on ruminant digestion. Pharmacological effects of saponins such as anti-inflammatory, diuretic, hypoglycaemic, antidiabetic, antiulcer and anti-ageing effects are also examined. From the literature reviewed, it can be concluded that saponins, in general, are toxic when administered intravenously but possess a lot of therapeutic potentials especially as cytotoxic agents.